A NOVEL WOUND DRESSING WITH SILKWORM COCOON SCAFFOLD TO FASTEN WOUND HEALING: AN IN VIVO STUDY USING RAT EXCISION WOUND MODEL - VALENTINA Y; JOHAN PANDIAN (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The study aimed to compare the effectiveness of silver-nano laden silkworm cocoon scaffold (SWCS), L-Ascorbic acid laden SWCS (AA-SWCS) over standard wet collagen sheet used for wound healing in rat incision wound model. Methods: A total of 24 Wistar rats (of either sex, pathogen free, 10–12 weeks old) were used in this study. SWCS was prepared and an excision wound model was carried out to study the wound healing capacity in four study groups. Dressings were made with silver nanoparticles SWCS (AgNP-SWCS), AA-SWCS and compared with wet collagen sheet regularly. Friedman’s test was used for analysis. Results: The results clearly indicate that both AgNP-SWCS and AA-SWCS significantly accelerate wound healing compared to the standard wet collagen sheet. The AgNP-SWCS outperformed the others in terms of wound contraction rate, histological quality of healing, and microbial load reduction. The AA-SWCS also showed enhanced healing properties, particularly in collagen synthesis and tissue organization. Conclusion: The study suggests that both AgNP-SWCS and AA-SWCS are highly effective alternatives to traditional collagen dressings for wound healing. These innovative scaffolds could represent a new frontier in wound care, providing enhanced healing rates, improved tissue quality, and reduced infection risks, ultimately leading to better patient outcomes.